Analysis on the Effect of Deposits and Financing on The Net Income (SHU) at KPN Al Ikhlas IAIN Batusangkar - R. Rizal; D. David; Sri Adella Fitri; R. Ramadanis (IQTISHADIA, 2018)
Cooperative is an institution founded by and for the members with the purpose to prosper the members with maximum achievement of outcome. The phenomenon that happened in Sharia civil servant cooperative Al-Ikhlas in IAIN Batusangkar from year of 2015 until the closing book in 2016, shows that member deposits and financing toward members has increased. Meanwhile, the net income is decreased. This phenomenon is interesting to investigate because it seems like the increasing of deposits and financing do not influence the net income. Consequently, This research aims to analysis the effect of deposit, such as special obligatory deposit, financing deposit and financing simultaneously and partially towards net income (SHU) at sharia civil servant cooperative (KPN) Al Ikhlas IAIN Batusangkar. This is a field research with quantitative approach during the year of 2015 and 2016 as the secondary data. The Result of this research shows that partially, merely financing that has effect towards net income (SHU) with significance level accost 6% that is 0.059 on wald value in the amount of 3,561.While basic contribution, obligatory deposit, special obligatory deposit, financing deposit have no significant effect on net income (SHU). Furhtermore, the amount of basic contribution effect, obligatory deposit effect, special obligatory deposit effect, financing deposit and financing simultaneously on net income (SHU) is 57.2%, while the remaining 42.8% is influenced by other factors that not examined in this research. It is suggested to the management of this sharia cooperative to find out another halal finance to increase financing so it can increase net income such as increasing member participation by gaining the amount of deposits.